ANALISA FAKTOR ADVERTISING DAN DIRECT MARKETING TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE APPLE - Putra Chairy (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2016)
This study is based on the premise that the importance of increasing sales by maximizing purchasing decisions. Factors that influence purchasing decisions are advertising (advertising) and direct marketing (direct marketing). Therefore, this study aimed to analyze the influence of advertising and direct marketing to the buying decision is made on a Smartphone Apple.Penelitian University student Amir Hamzah Medan.This type of research is using associative approach, the research data is primary data and secondary data. This study population mahas wearing Apple Smartphone, the sample of 52 respondents. Data analysis using multiple linear regression test.The results obtained as well as a conclusion of this study were: advertising (advertising) positive and significant impact on purchasing decisions, and direct marketing (direct marketing) positive and significant effect on purchasing decisions either partially tested or tested simultaneously. The researchers suggest that companies should be able to maximize efforts to improve purchasing decisions on sales.